Proinflammatory response of human trophoblastic cells to Brucella abortus infection and upon interactions with infected phagocytes - Fernández, Andrea G. (2016)
Trophoblasts are targets of infection by Brucella spp. but their role in the pathophysiology of pregnancy complications of brucellosis is unknown. Here we show that Brucella abortus invades and replicates in the human trophoblastic cell line Swan-71 and that the intracellular survival of the bacterium depends on a functional virB operon. The infection elicited significant increments of interleukin 8 (IL8), monocyte chemotactic protein 1 (MCP-1), and IL6 secretion, but levels of IL1beta and tumor necrosis factor-alpha (TNF-alpha) did not vary significantly. Such proinflammatory response was not modified by the absence of the Brucella TIR domain-containing proteins BtpA and BtpB. The stimulation of Swan-71 cells with conditioned medium (CM) from B. abortus-infected human monocytes (THP-1 cells) or macrophages induced a significant increase of IL8, MCP-1 and IL6 as compared to stimulation with CM from non-infected cells. Similar results were obtained when stimulation was performed with CM from infected neutrophils. Neutralization studies showed that IL1beta and/or TNF-alpha mediated the stimulating effects of CM from infected phagocytes. Reciprocally, stimulation of monocytes and neutrophils with CM from Brucella-infected trophoblasts increased IL8 and/or IL6 secretion. These results suggest that human trophoblasts may provide a local inflammatory environment during B. abortus infections either through a direct response to the pathogen or through interactions with monocytes/macrophages or neutrophils, potentially contributing to the pregnancy complications of brucellosis.